ANALISIS SEMIOTIK: PENANDA DAN PETANDA DALAM MAULID SYARAF AL-ANAM KARYA AL-HARIRI (PENDEKATAN FERDINAND DE SAUSSURE) - Adelawati, Munzila; Sudarmawan, Habib; Ambarwati, Putri (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Since the Jahili era, Arab societies have shown great appreciation for literature. Their thoughts, ideas and thoughts were often reflected through literary works created by their poets. One form of literature that was phenomenal and recognized by the Arabs was poetry. Arabic poetry is famous for a variety of themes, such as lamentation, love, politics, warfare, and praise. However, understanding poetry is not easy because there are signifiers and signs that need to be deciphered. This study aims to reveal the signifiers and signs used by Arab poets in their poetry texts, especially in Al-Hariri's Maulid Syaraf Al-Anam. Qualitative descriptive method is used by collecting data through literature study. The data taken in the form of words or phrases from the Syaraf Al-Anam maulid, then analyzed using the theories put forward by Ferdinand de Saussure. Ferdinand de Saussure, as the originator of the semiotic branch in linguistic studies. The results of this study indicate the existence of signifiers and signs in the maulid poem Syaraf Al-Anam by Al-Hariri, which consists of fourteen stanzas. Some examples of signifiers and signs found include As-Salamu, Al-Badru, Al-Misku, At-Tibu, Al-Kahfa, Al-Ghomamah, Al-Misbahu, Ar-Rasaili, Ar-Ra'su, At-Tihamah Al-Qiblataini, and Al-Mu'jizat.